Mothers' Caregiving during COVID: The Impact of Divorce Laws and Homeownership on Women's Labor Force Status - Cynthia Bansak; Shoshana Grossbard; Crystal (Ho Po) Wong (Institute of Labor Economics (IZA), 2021)
We investigate women's likelihood of withdrawing from paid labor to care for children and help them with schoolwork as a result of COVID and school closures. Were women more likely to shift out of paid labor in states where property-division rules would better protect the financial interests of stay-at-home parents? Such higher protection is offered in states with community property regimes or with homemaking provisions, the alternative being equitable-division and no homemaking provisions. We use monthly data from the U.S. Current Population Survey and compare the labor force participation of women with children in grades K-6 between 2019 and 2020, before and after COVID started. We find an association between marital property laws offering women more financial protection and women's labor supply response to COVID-19, especially among non-immigrants.
Keywords: J13; J16; J2; I18; 330; COVID-19; labor force; schools; community property; divorce